Diaper dermatitis: Effect of UVB-radiation or antifungal therapy. - Runeman, B.; Borres, M.P.; Faergemann, J.; Larkö, O. (European Journal of Pediatric Dermatology, 2000)
Diaper dermatitis is experienced by almost every child in diaper wearing age. The main factors causing the dermatitis are skin humidity, mechanical abrasion, irritants in urine and feces, fecal enzyme activity and microbial growth. This investigation of children (n = 39, age < 18months), was aimed at studying the growth of microorganisms and the rash development and at evaluating the effect of UVB radiation compared to a combined antifungal-hydrocortisone cream. Candida albicans was found in the dermatitis area in 57% of the children and Staphylococcus aureus was found in 46%. The growth of microorganisms was considerably greater in the area of dermatitis than on unaffected skin at another site under the diaper. For all species found, positive cultures were more frequent among girls than among boys. Twentysix children were treated either with UVB-radiation or with a combined antifungal-hydrocortisone cream. Both therapies showed a 71-75% improvement rate after one week of treatment. All cases that were assessed as moderate or severe irritation were improved by at least one step (on a three-point scale) after one week. UVB therapy could be a useful alternative when conventional therapies fail or when they should be avoided due to risks of adverse effects.